Raspberry Pi user guide - Upton, Eben; Halfacree, Gareth ([Place of publication not identified] : John Wiley & Sons, 2016)
Learn the Raspberry Pi 3 from the experts! Raspberry Pi User Guide, 4th Edition is the "unofficial official" guide to everything Raspberry Pi 3. Written by the Pi's creator and a leading Pi guru, this book goes straight to the source to bring you the ultimate Raspberry Pi 3 manual. This new fourth edition has been updated to cover the Raspberry Pi 3 board and software, with detailed discussion on its wide array of configurations, languages, and applications. You'll learn how to take full advantage of the mighty Pi's full capabilities, and then expand those capabilities even more with add-on technologies. You'll write productivity and multimedia programs, and learn flexible programming languages that allow you to shape your Raspberry Pi into whatever you want it to be. If you're ready to jump right in, this book gets you started with clear, step-by-step instruction from software installation to system customization. The Raspberry Pi's tremendous popularity has spawned an entire industry of add-ons, parts, hacks, ideas, and inventions. The movement is growing, and pushing the boundaries of possibility along with it--are you ready to be a part of it? This book is your ideal companion for claiming your piece of the Pi. Get all set up with software, and connect to other devices Understand Linux System Admin nomenclature and conventions Write your own programs using Python and Scratch Extend the Pi's capabilities with add-ons like Wi-Fi dongles, a touch screen, and more The credit-card sized Raspberry Pi has become a global phenomenon. Created by the Raspberry Pi Foundation to get kids interested in programming, this tiny computer kick-started a movement of tinkerers, thinkers, experimenters, and inventors
Playing Music at the ConsoleDedicated HTPC with OSMC; Streaming Internet Media; Streaming Local Network Media; Configuring OSMC; Chapter 9 The Pi as a Productivity Machine; Using Cloud-Based Apps; Using LibreOffice; Image Editing with the Gimp; Part 3 Programming the Pi; Chapter 10 An Introduction to Scratch; Introducing Scratch; Example 1: Hello World; Example 2: Animation and Sound; Example 3: A Simple Game; Interfacing Scratch with Hardware; Further Reading; Chapter 11 An Introduction to Python; Introducing Python; Example 1: Hello World; Example 2: Comments, Inputs, Variables, and Loops.
Print version record.
Includes bibliographical references.
John Wiley and Sons
Keywords: Raspberry Pi (Computer); Microcomputers -- Programming; Computer programming; Raspberry Pi (Ordinateur); Micro-ordinateurs -- Programmation; Programmation (Informatique); computer programming; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Computer programming; Microcomputers -- Programming; Raspberry Pi (Computer)